76‐3: Invited Paper: Slim MiniLED Backlight for HDR‐Compatible Mobile Displays. Issue 1 (28th June 2022) - Watanabe, Hisashi; Masuda, Takeshi; Yasunaga, Hirotoshi; Tanaka, Atsuyuki; Takase, Kenji
Abstract : Recently, ultra‐slim, direct lit backlights with 2‐dimensional local dimming control have come to the forefront because of increased demand for HDR compatible LCDs for mobile devices. We present a newly developed Mini‐LED backlight that offers an effective solution to those demands.